Differences in the Effect of Using Sterile Water for Irrigation and Normal Saline Washing to Peritoneal Adhesion Post-Laparotomy on White Rats - Octaviani Octaviani; Agus Rahardjo; Untung Alifianto; Setya Anton (The Indonesian Biomedical Journal, 2017)
BACKGROUND: Peritoneal adhesion is a side effect of abdominal surgery that often occurs. Many efforts were made in abdominal surgery to prevent or minimize the occurrence of this adhesion. One way to reduce the risk of bowel adhesions is through washing peritoneum method, so the differences in the use of washing solution on the incidence of adhesions after laparotomy surgery need to be investigated. The objective of this study is to determine differences in the effect of using sterile water and normal saline for washing irrigation to peritoneal adhesions after laparotomy in white rats.METHODS: This was an experimental study. Thirty-two sample of white rats were divided into two groups, group A and Group B, each group consists of 16 rats. Group A got washing using normal saline and group B got washing using sterile water for irrigation in laparotomy procedure to assess the peritoneal adhesion microscopically after relaparotomy. RESULTS: This study was conducted in April-May 2016. The founding of peritoneal adhesion after laparotomy in white rats using sterile water for irrigation in grade 1 were seven samples, grade 2 were five samples and grade 3 were four samples. Meanwhile, the founding of peritoneum adhesion after laparotomy using normal saline grade 1 are two samples, grade 2 are five samples, and grade 3 are nine samples. Statistically, significant differences were found (p<0.05).CONCLUSION: Some risk factors can lead to adhesion, such as trauma surgery, tissue ischemia, infection blood and foreign body irritating. Intraperitoneal irrigation with sterile water for irrigation is better than the use of normal saline in preventing peritoneal adhesion.KEYWORDS: peritoneal adhesions, sterile water for irrigation, normal saline